The Use of Zamzam Water and Pumpkin Fruit in Science and Islamic Perspective - Mansur, Sugeng Ali; Hermayanti, Diana Dwi; Rahmadinata, Yusril Dwi; Maharani, Kumoratih Eka; Mohamed, Moram Gamal; Amiruddin, Muhammad (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 1 (2022): Proceeding Annual Symposium on Hajj and Umrah Medicine, 2022)
Zam-zam water is a holy spring for religious and medicinal purposes for Muslims. Zam Zam Water is located 21 meters to the east of the Kaaba. Zam Zam water is rich in beneficial elements and chemical composition of up to 2,000 mg/lt. So that Zam Zam water has benefits as an anticancer, maintaining healthy teeth and mouth, stimulating the reproductive system, and antioxidants. Pumpkin has low calories that are suitable for diets. Pumpkin contains a source of nutrients such as carotene and fiber and is high in protein. It is hoped that writing this article will bring benefits to enrich the treasures of Zam Zam water and pumpkin, both from an Islamic and health perspective.